Underreporting and Missed Opportunities for Uptake of Intermittent Preventative Treatment of Malaria in Pregnancy (IPTp) in Mali. - Emily A Hurley; Steven A Harvey; Namratha Rao; Niélé Hawa Diarra; Meredith C Klein; Samba I Diop; Seydou O Doumbia (PLoS ONE, 2016)
To identify factors contributing to low uptake of intermittent preventive treatment of malaria in pregnancy with sulfadoxine-pyrimethamine (IPTp-SP) in rural Mali.We conducted secondary data analysis on Mali's 2012-2013 Demographic and Health Survey (DHS) to determine the proportion of women who failed to take IPTp-SP due to ineligibility or non-attendance at antenatal care (ANC). We also identified the proportion who reported taking other or unknown medications to prevent malaria in pregnancy and those who did not know if they took any medication to prevent malaria in pregnancy. We conducted qualitative interviews, focus groups and ANC observations in six rural sites in Mali's Sikasso and Koulikoro regions to identify reasons for missed opportunities.Our secondary data analysis found that reported IPTp-SP coverage estimates are misleading due to their dependence on a variable ("source of IPTp") that is missing 62% of its data points. Among all women who gave birth in the two years prior to the survey, 56.2% reported taking at least one dose of IPTp-SP. Another 5.2% reported taking chloroquine, 1.9% taking another drug to prevent malaria in pregnancy, 4.4% not knowing what drug they took to prevent malaria, and 1.1% not knowing if they took any drug to prevent malaria. The majority of women who did not receive IPTp-SP were women who also did not attend ANC. Our qualitative data revealed that many health centers neither administer IPTp-SP by directly observed therapy, nor give IPTp-SP at one month intervals through the second and third trimesters, nor provide IPTp-SP free of charge. Women generally reported IPTp-SP as available and tolerable, but frequently could not identify its name or purpose, potentially affecting accuracy of responses in household surveys.We estimate IPTp-SP uptake to be significantly higher than stated in Mali's 2012-13 DHS report. Increasing ANC attendance should be the first priority for increasing IPTp-SP coverage. Reducing cost and access barriers, ensuring that providers follow up-to-date guidelines, and improving patient counseling on IPTp-SP would also facilitate optimal uptake.